1991
DOI: 10.1128/iai.59.6.1984-1990.1991
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibody response to Pseudomonas aeruginosa antigens during corneal infection

Abstract: Previous studies in our laboratory have indicated that naturally resistant, inbred DBA/2J mice mount a greater serum antibody response to Pseudomonas aeruginosa 19660 than susceptible C57BL/6J mice. However, the specificity of the antibody produced was not known. The present study examines the specificity and kinetics of the humoral response of these mouse strains to potential virulence factors produced by the organism during both a primary and a secondary corneal infection administered 4 weeks after the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Immune response to infection. Previous works have established the pattern of immune responses to P. aeruginosa antigens during corneal infection with strain 19660 (20,22,23). In this study, we sought to determine whether P. aeruginosaspecific serum IgG could be elicited after infection with lowlevel challenge doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune response to infection. Previous works have established the pattern of immune responses to P. aeruginosa antigens during corneal infection with strain 19660 (20,22,23). In this study, we sought to determine whether P. aeruginosaspecific serum IgG could be elicited after infection with lowlevel challenge doses.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, scratches are made on the corneas of mice anesthetized with inhalants such as ether, and the challenge strain of P. aeruginosa is applied in a small volume (5 l). However, only a few strains of P. aeruginosa have been reported to be pathogenic under these conditions, and inocula of 10 7 to 10 8 CFU are needed to initiate infection (1,2,11,15,20,22,23). The limited number of virulent strains and the need for high-challenge inocula has restricted the use of this model in the evaluation of microbial and host factors involved in the pathogenesis of P. aeruginosa corneal infections.…”
mentioning
confidence: 99%
“…Recent substrate specificity studies that examined the serum antibody response to various * Corresponding author. 885 exoenzymes and surface antigens of P. aenrginosa during corneal infection showed that susceptible C57BL/6 mice not only were capable of responding to flagella and the exoenzymes exotoxin A and phospholipase C during both primary and secondary infection but in some cases exceeded the response mounted by DBA/2 mice (29). Neither mouse strain produced antibody to elastase or alkaline protease after either primary or secondary infection (29).…”
mentioning
confidence: 99%
“…885 exoenzymes and surface antigens of P. aenrginosa during corneal infection showed that susceptible C57BL/6 mice not only were capable of responding to flagella and the exoenzymes exotoxin A and phospholipase C during both primary and secondary infection but in some cases exceeded the response mounted by DBA/2 mice (29). Neither mouse strain produced antibody to elastase or alkaline protease after either primary or secondary infection (29). These data suggested that the hyporesponsiveness of C57BL/6 mice is restricted to as-yet-unidentified antigens present on the surfaces of P. aeruginosa cells.…”
mentioning
confidence: 99%
“…Antigenic properties of exoproducts P. aeruginosa produces a number of secreted virulence factors including exotoxin A, exoenzyme S, proteases I (neutral protease) and III (alkaline phosphatase), elastase, hemolysins (thermolabile phosphatase C and thermostable acid glycolipid), enter- Table 1 Probable role of extracellular products of P. aeruginosa in virulence and immunogenicity Extracellular antigen Role in virulence Antibody or protective response Reference Proteases : (i) Elastase Induces hemorrhagic lesions and necrosis, Abs in patients with chronic and/or active [18^20] tissue invasion, destruction of host defenses, P. aeruginosa infections; provide protections against e.g. complements and opsonins severe lung lesions in animal models (ii) Alkaline protease Destruction of non-speci¢c host defenses, Abs detected in burn wound patients [21] tissue invasion Phospholipase C Destruction of pulmonary surfactant Rise in Ab titer in CF patients colonized with [22,23] Generation of in£ammatory mediators P. aeruginosa, and in animal model infections Rhamnolipids…”
Section: Introductionmentioning
confidence: 99%